Arabidopsis long-chain acyl-CoA synthetase 1 (LACS1), LACS2, and LACS3 facilitate fatty acid uptake in yeast - Pulsifer, Ian P (Plant physiology and biochemistry : PPB, 2012)
Copyright © 2011 Elsevier Masson SAS. All rights reserved.